2010
DOI: 10.1128/aem.00915-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cryptosporidium Species and Genotypes in Scottish Raw and Drinking Waters during a One-Year Monitoring Period

Abstract: We analyzed 1,042 Cryptosporidium oocyst-positive slides (456 from raw waters and 586 from drinking waters) of which 55.7% contained 1 or 2 oocysts, to determine species/genotypes present in Scottish waters. Two nested PCR-restriction fragment length polymorphism (RFLP) assays targeting different loci (1 and 2) of the hypervariable region of the 18S rRNA gene were used for species identification, and 62.4% of samples were amplified with at least one of the PCR assays. More samples (577 slides; 48.7% from raw w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 28 publications
7
43
0
1
Order By: Relevance
“…However, further research is required to better understand the zoonotic importance of C. andersoni and it has not been identified in humans in Jordan in the one previous genotyping study (Hijjawi et al, 2010). C. andersoni is also frequently the dominant species in source and tap water in China and the UK (Feng et al, 2011;Nichols et al, 2010), suggesting that cattle may be the primary source of contamination. The C. parvum subtype identified in cattle (IIaA16G1R1) is a common subtype as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…However, further research is required to better understand the zoonotic importance of C. andersoni and it has not been identified in humans in Jordan in the one previous genotyping study (Hijjawi et al, 2010). C. andersoni is also frequently the dominant species in source and tap water in China and the UK (Feng et al, 2011;Nichols et al, 2010), suggesting that cattle may be the primary source of contamination. The C. parvum subtype identified in cattle (IIaA16G1R1) is a common subtype as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques that can also be used for cyst or oocyst purification purposes include density gradient, saturated-salt flotation, and continuous flow centrifugation, continuous flow filtration, and flow cytometry with cell sorting (45,251,299). Additional molecular methods are currently available for the identification of protozoa in water samples by detection of pathogen-specific genes or SSU rRNA (292,375). For example, nested PCR-RFLP assays are used to target different loci (1 and 2) of the hypervariable region of the 18S rRNA gene for identification of different Cryptosporidium spp.…”
Section: Detection Of Protozoa In Water Samplesmentioning
confidence: 99%
“…For example, nested PCR-RFLP assays are used to target different loci (1 and 2) of the hypervariable region of the 18S rRNA gene for identification of different Cryptosporidium spp. in water (292). Other PCRs have been developed to amplify the COWP gene (9).…”
Section: Detection Of Protozoa In Water Samplesmentioning
confidence: 99%
“…In addition, many studies have reported that C. andersoni, which is predominantly a parasite of adult cattle, C. ubiquitum, which is a common Cryptosporidium species in sheep and C. parvum are the dominant Cryptosporidium species detected in watersheds and raw and drinking water (Yang et al 2008;Ruecker et al 2007;Nichols et al 2010;Smith and Nichols, 2010). In addition, the high density of cattle and sheep across Australia, which contribute a large volume of manure to catchments indicate that they are the main species that present a risk to public health in Australian catchments.…”
Section: S P E C I E S a N D S T R A I N S O F C R Y P T O S P O R I mentioning
confidence: 99%